Unique clinical characteristics, autoantibodies and medication use in Native American patients with systemic lupus erythematosus (2018)
Objective: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with varied morbidity and mortality. We assessed clinical presentations, autoantibody specificities and therapeutic interventions in Native American (NA) patients with SLE. Methods: Patients with SLE meeting 1997 American College of Rheumatology classification criteria (n=3148) were enrolled between 1992 and 2010 in the multiethnic, cross-sectional Lupus Family Registry and Repository. Clinical, demographic and therapeutic information were extracted from medical records using a standardised form and formalised training. Autoantibodies were assessed by indirect immunofluorescence (antinuclear antibodies (ANA) and antidouble-stranded DNA), precipitin (ENA) and ELISA (IgG and IgM anticardiolipins). Results: NA patients met SLE classification at a younger age (29.89±12.3 years) than European Americans (EA; 32.02±12.87, P=0.0157) and a similar age to African-Americans (AAs) and Hispanics (HIS). More NA patients had concurrent rheumatic diseases or symptoms, such as Raynaud's phenomenon, interstitial lung disease, Sjögren's syndrome and systemic sclerosis. Compared with EAs, NAs were more likely to have high-titre ANA (≥1:3240; P<0.0001) and had more SLE-associated autoantibodies. Autoantibodies with unknown specificities were more common in NAs (41%) compared with other racial/ethnic groups in this collection (AA: 24%, P=0.0006; EA: 17%, P<0.0001; HIS: 23%, P=0.0050). Fewer NA patients used hydroxychloroquine (68%) compared with others (AA: 74%, P=0.0308; EA: 79%, P=0.0001, HIS: 77%, P=0.0173); this was influenced by lower hydroxychloroquine use in NA patients from Latin America (32%). NA patients had higher rates of methotrexate use (28%) compared with AA (18%, P=0.0006) and HIS patients (14%, P=0.0003), higher azathioprine use (38%) compared with EA patients (30%, P=0.0105) and higher mycophenolate mofetil use (26%) compared with EA (17%, P=0.0012) and HIS patients (11%, P<0.0001). Conclusions: NA patients are diagnosed with SLE earlier in life and present worse concurrent rheumatic disease symptoms than EA patients. NA patients also are more likely to have expanded autoantibody profiles and precipitins of unknown specificities. © 2018 Article author(s).